Systemic immune classification related to immune exhaustion evaluates the clinical response of patients with HBV-HCC after transarterial chemoembolization - Yu, Lihua; Liu, Xiaoli; Hu, Ying; Yan, Huiwen; Xie, Yuqing; Shang, Zimeng; Liang, Yuling; Shi, Wanxin; Du, Juan; Jiang, Yuyong; Zhang, Henghui; Yang, Zhiyun (Frontiers in Immunology, 2025)
Transarterial chemoembolization (TACE) has the potential to activate the immune system and regulate the tumor microenvironment. This study assesses the clinical response of patients with HBV-related hepatocellular carcinoma (HBV-HCC) after TACE treatment based on systemic immune classification (SIC). A total of 80 patients with HBV-HCC were assessed for the peripheral blood immune exhaustion phenotype and immune proteins through a combination of “Olink High Sensitivity Plasma Proteomics” and “Multicolor Flow Cytometry.” An unsupervised clustering algorithm was employed to classify various immune subtypes and identify core indicators that evaluate the response of SIC to TACE treatment. The application of these two technologies as novel approaches for detecting HBV-HCC provides synergistic insights into disease mechanisms and patient prognosis. Based on the combination of immune exhaustion phenotypes and immune proteins, we developed SIC that classified the subjects into three clusters: Cluster 1, Cluster 2, and Cluster 3. Cluster 3 was associated with poor clinical characteristics, unfavorable prognosis, and elevated levels of immune checkpoint expression. This risk scoring system is capable of predicting the overall survival of patients at various time points, with receiver operating characteristic areas exceeding 0.8. This study establishes SIC method to predict the clinical response of HBV-HCC patients after TACE treatment, providing new guidance for future immunotherapy and identification of non-invasive biomarkers.